2018
DOI: 10.1016/j.acmx.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de las características de la disección aórtica en la población mexicana mediante angiotomografía computarizada

Abstract: AD is an emergency in which diagnosis and timely management are essential to improve prognosis. In the sample presented here, a significant association was found in patients with a history of Marfan syndrome and abdominal aneurysms with dissections according to the Stanford classification. The rest of the independent variables did not show any significant association, probably related to the size of the sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The mean age in Brazil was roughly 54.4 years [58] . Burboa-Noriega et al reported a mean age of 54.5 years in Mexico [59] .…”
Section: Age-based Differencesmentioning
confidence: 99%
“…The mean age in Brazil was roughly 54.4 years [58] . Burboa-Noriega et al reported a mean age of 54.5 years in Mexico [59] .…”
Section: Age-based Differencesmentioning
confidence: 99%